Drug-Induced Immune Hemolytic Anemia due to Amoxicillin-Clavulanate: A Case Report and Review - Chan Gomez, Janet (Cureus, 2020)
Drug-induced immune hemolytic anemia (DIIHA) is a rare cause of anemia. It is often difficult to distinguish from other causes of hemolytic anemia, thereby delaying diagnosis and treatment. Antibiotics, including penicillins and cephalosporins, are the drugs most often implicated in the development of DIIHA. Discontinuation of the offending agent is often sufficient for treatment. Here, we review the case of a 25-year-old Caucasian female who presented with jaundice and generalized weakness in the setting of outpatient treatment with amoxicillin-clavulanate due to sinus infection. Laboratory testing revealed transaminitis and hemolytic anemia. Direct antiglobulin test (DAT) revealed negative IgG and positive anti-C3. Cold agglutinin titer and Donath-Landsteiner test were negative. The patient was diagnosed with DIIHA most likely due to amoxicillin. She improved with drug cessation and a short course of glucocorticoids. Mechanism of DIIHA, workup, and management are subsequently reviewed.